Two-dimensional photoelastic stress analysis of traumatized incisor. - (:unkn) unknown (My University, 2001)
In this study, stress of traumatized incisor and the effect of stress on tooth and alveolar bone was studied with two-dimensional photoelasticity. Two homogeneous two-dimensional maxillary central incisor models were prepared. Loads were applied to the labial side of incisal edge and middle third of the crown at angles of 45 degrees and 90 degrees. It was observed that stress was increased on teeth and alveolar bone when load was applied 90 degrees on labial side of incisal edge.